MENINGKATAN MUTU PENDIDIKAN MELALUI PENERAPAN MANAJEMEN BERBASIS SEKOLAH - Nurdin Mansur (Jurnal Ilmiah Didaktika, 2013)
Administration has a wider meaning than management, for management is the core of administration. Educational management is a systematic and comprehensive process of cooperation to reach the goals of national education. Through educational management, everything related to the management process of education is done to achieve the goal of organization either for short, mid, or long term goals. School based management has several characteristics to empower many things, such as: small group formation, transfer of responsibility, leader made of participant, teacher as a facilitator, a democratic process and flexible relationship. Everything in school- based management is decided based on mutual understanding among the equal participant through a democratic way. Through school-based management it is hoped that headmasters, teachers, administrative staffs and also society can implement the education based on the era development and characteristic of the environment as well as the demand of global education.